2012
DOI: 10.1590/s1413-35552012005000043
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain, profile and quality of life of individuals with sickle cell disease

Abstract: Background: Sickle cell disease is a prevalent condition in Brazil. Its clinical presentation includes vascular occlusion that result in ischemia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…and adult patients [19,20]. Musculoskeletal/deep-tissue pain has been found to be present at multiple sites including the arms, chest and lower back in a questionnaire-based study of 27 adult patients with mean age of 31.77 years [22].…”
Section: Subjects With Scd Transgenic Mice Expressing Sickle Hemoglobinmentioning
confidence: 99%
“…and adult patients [19,20]. Musculoskeletal/deep-tissue pain has been found to be present at multiple sites including the arms, chest and lower back in a questionnaire-based study of 27 adult patients with mean age of 31.77 years [22].…”
Section: Subjects With Scd Transgenic Mice Expressing Sickle Hemoglobinmentioning
confidence: 99%
“…22 It also agrees with the study of Chinawa et al, 19 that reported lower limb and upper limb pain as the common cause of admitted cases of SCA in their study. In the same line 23 reported pain crises including painful bone crisis to occur in all participants in their study as it is the most prevalent cause of health care consultation.…”
Section: Discussionmentioning
confidence: 65%
“…26 The disease is thought to have a high tropism for patients with SCA. 23 However, Zanoni et al, 3 are of the opinion that in addition to the sensitivity of salmonella with SCA patients, the bad hygienic life conditions of the concerned population can explain an endemicity of salmonellosis in some regions especially in the developing countries, therefore buttressing the high prevalence of osteomyelitis among SCA patients in a developing country like Nigeria. The prevalence of septic arthritis in the current study is similar with previous reported prevalence of 6-15%.…”
Section: Discussionmentioning
confidence: 99%
“…Ohara et al [78] verified the relation between musculoskeletal pain in persons with sickle-cell anaemia, and their quality of life, as well as their social and economic characteristics. These researchers used the NMQ and the SF-36 health questionnaire.…”
Section: Pathologies Health and Ageingmentioning
confidence: 98%